Hands-on reactive programming with Reactor : build reactive and scalable microservices using the Reactor framework - Sharma, Rahul (Packt Publishing, 2018)
Hands-On Reactive Programming with Reactor presents a variety of examples which show how to use the Reactor framework to handle asynchronous code. In reactive programming, Reactor is a foundation for all its asynchronous applications on the JVM.